Development of the case method in anti-corruption education courses in physical education and sports - Aprial. M, Benny; Rahmat, Zikrur; Alfiansyah Putra Karo-karo, Alan; Giawa, Epenetus (Universitas Suryakancana, 2023)
The purpose of this study is to create a course design for Anti-Corruption Education at Sekolah Tinggi Olahraga dan Kesehatan Bina Guna that incorporates the case method idea into the Physical Education Study Program. According to Borg and Gall's research and development research, it took more than three months to complete, with the following details: Needs analysis, Planning for model creation, Creation of exercise model designs, Model modification and expert validation, Trials and adjustments in small groups, Field tests and modificationsThe research's findings demonstrate that: the case method's development for anti-corruption education courses is appropriate for use as a learning tool, as evidenced by the expert validation results in the case method aspect, which obtained percentages of 81.25%, 94.61%, and excellence of 79.17%; the material expert validation results in the learning design aspect, which obtained percentages of 80%, 81.25%, and 85% in the excellence aspect; and the student assessments results in the case method aspect, which obtained a percentage of 78, 94%. The research conclusion is one way to train students' talents in rhetorical, realistic and critical thinking, as well as basic research is through case method-based learning which originates from field observations and investigations and the findings of this research are consistent with other research regarding the case approach of anti-corruption teaching programs in education physical.Key words: development, case method, anti-corruption education.